Advances in Unconventional Oil and Gas - Tao, Shu; Zhang, Dengfeng; Huang, Huazhou; Wang, Shuoliang; Meng, Yanjun (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the latest progress in unconventional oil and gas (such as coalbed methane, shale gas, tight gas, heavy oil, hydrate, etc.) exploration and development, including reservoir characterization, gas origin and storage, accumulation geology, hydrocarbon generation evolution, fracturing technology, enhanced oil recovery, etc. Some new methods are proposed to improve the gas extraction in coal seams, characterize the relative permeability of reservoirs, improve the heat control effect of hydrate-bearing sediment, improve the development efficiency of heavy oil, increase fracturing effectiveness in tight reservoirs, etc.